2014
DOI: 10.1073/pnas.1402251111
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic neurotransmission links solitary chemosensory cells to nasal inflammation

Abstract: Solitary chemosensory cells (SCCs) of the nasal cavity are specialized epithelial chemosensors that respond to irritants through the canonical taste transduction cascade involving Gα-gustducin and transient receptor potential melastatin 5. When stimulated, SCCs trigger peptidergic nociceptive (or pain) nerve fibers, causing an alteration of the respiratory rate indicative of trigeminal activation. Direct chemical excitation of trigeminal pain fibers by capsaicin evokes neurogenic inflammation in the surroundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
244
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(253 citation statements)
references
References 50 publications
6
244
0
3
Order By: Relevance
“…Furthermore, in vivo studies demonstrated that mice exposed to acyl-homoserine lactones via the retronasal stream experienced significant reductions in respiratory rate, suggesting that interactions between bacterial acyl-homoserine lactones and chemosensory cells are capable of inducing responses indicative of nasal trigeminal irritants (304). The activation of nasal solitary chemosensory cells by acyl-homoserine lactones triggers a proinflammatory response (328); this response may damage the integrity of the epithelium and enable bacteria to access the trigeminal nerve endings. Once bacteria have penetrated the epithelium, they may potentially travel along the olfactory and/or trigeminal nerves to the brain, within axons, between the axons, within the surrounding glia (olfactory ensheathing cells or Schwann cells), or between the glia and the connective tissue sheath (perineurium) that contains the nerve bundle.…”
Section: Pathogens That Enter the Brain Through The Nose Bacteriamentioning
confidence: 99%
“…Furthermore, in vivo studies demonstrated that mice exposed to acyl-homoserine lactones via the retronasal stream experienced significant reductions in respiratory rate, suggesting that interactions between bacterial acyl-homoserine lactones and chemosensory cells are capable of inducing responses indicative of nasal trigeminal irritants (304). The activation of nasal solitary chemosensory cells by acyl-homoserine lactones triggers a proinflammatory response (328); this response may damage the integrity of the epithelium and enable bacteria to access the trigeminal nerve endings. Once bacteria have penetrated the epithelium, they may potentially travel along the olfactory and/or trigeminal nerves to the brain, within axons, between the axons, within the surrounding glia (olfactory ensheathing cells or Schwann cells), or between the glia and the connective tissue sheath (perineurium) that contains the nerve bundle.…”
Section: Pathogens That Enter the Brain Through The Nose Bacteriamentioning
confidence: 99%
“…However, while the expression of taste receptors in the sinonasal epithelium is ubiquitous on disparate cell types, including ciliated cells and solitary chemosensory cells, in the tongue taste receptor expression is confined to type II cells within the taste buds. Furthermore, while some bitter taste receptors in the airway are upstream of a nervous signaling cascade, others act in a cell-autonomous fashion only [8,19,20]. When a ligand binds to a taste GPCR, there is activation of phospholipase C isoform β2 (PLCB2), which triggers downstream inositol 1,4,5-trisphosphate (IP3) production.…”
Section: Taste Receptor Physiologymentioning
confidence: 99%
“…These cells are immunoreactive with α-gustducin, a taste signalling component, and they share many similarities with taste bud cells [28]. Because of their rarity, they are difficult to isolate experimentally [19]. Solitary chemosensory cells express both sweet and bitter taste receptors that are capable of responding to a variety of compounds [8,20,27,56,57].…”
Section: Taste Receptors On Solitary Chemosensory Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing receptors and signaling cascades classically associated with the detection of bitter tastants, SCCs effectively enhance the chemosensory repertoire of the TN, facilitating its indirect activation by hydrophilic compounds that cannot readily cross epithelial layers to reach chemosensitive TN fibers. These specialized cells are present in functionally relevant areas of the respiratory epithelia of humans and rodents, where they respond to irritants and bacterial metabolites, trigger respiratory and other responses, and excite TN fibers upon activation (Saunders et al 2014;Barham et al 2013;Tizzano et al 2010;Finger et al 2003).…”
Section: Introductionmentioning
confidence: 99%